2016
DOI: 10.21315/mjms2016.23.5.10
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Anthropomic Study of Cranial Capacity among Ukwuani People of South Nigeria

Abstract: Background: Cranial capacity is used as a measure of brain volume and has a relationship with age and gender. The purpose of this study was to provide normative data and population-, age-and gender-specific regression formulae related to cranial capacity using head dimensions among the Ukwuani people of Nigeria.Methods: This study included 605 subjects grouped according to age as follows: 6-12 years, 13-19 years and ≥20 years. A cross-sectional study design using multistage sampling technique was adopted. Head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Analysis of the effect size showed only a small effect size for sex. The values of anthropological parameters of younger school age were presented in other countries, e.g., from Africa (Nigeria) [17,18]; from South America (Brazil) [38,40]; from Taiwan [11]; from India [31,57]; from Malaysia [9]; from Ireland [42]; from Japan [29,30,39]; and from Turkey [27].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the effect size showed only a small effect size for sex. The values of anthropological parameters of younger school age were presented in other countries, e.g., from Africa (Nigeria) [17,18]; from South America (Brazil) [38,40]; from Taiwan [11]; from India [31,57]; from Malaysia [9]; from Ireland [42]; from Japan [29,30,39]; and from Turkey [27].…”
Section: Discussionmentioning
confidence: 99%
“… 19 Furthermore, the mean cranial capacity of Korean males was 1594 cm3 and that of Korean females was 1425 cm 3 . 20 Additionally, studies from Africa have suggested that the mean African cranial capacity differs from that of Asians and Americans: the cranial capacity for African males was 1460 cm 3 and for females was 1129 cm 3 . 20 The current study included mastoid air sinuses in calculation of cranial capacity.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Additionally, studies from Africa have suggested that the mean African cranial capacity differs from that of Asians and Americans: the cranial capacity for African males was 1460 cm 3 and for females was 1129 cm 3 . 20 The current study included mastoid air sinuses in calculation of cranial capacity. Additionally, the measurements of mastoid air sinuses have been shown to be affected by other factors such as age, sex and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that cranial capacity does not change in size during the rest of life [13]. The average cranial capacity of humans was suggested to be 1400 cm 3 (Milner, 1990), but other studies have suggested variations due to various factors such as race, environment, age, gender and hereditary factors [14,15]. Applying the Slovin's simplified formula for proportions, a sample size of 399.98 (approximately 400) adolescents was calculated to be used.…”
Section: Introductionmentioning
confidence: 99%